2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27860
|View full text |Cite
|
Sign up to set email alerts
|

Board # 46 : Perceived Self-Efficacy of Master's in Engineering Students Regarding Software Proficiency and Engineering Acumen

Abstract: focuses on strategies for design innovations through divergent and convergent thinking as well as through deep needs and community assessments using design ethnography, and translating those strategies to design tools and education. She teaches design and entrepreneurship courses at the undergraduate and graduate levels, focusing on front-end design processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The work in this paper is part of that larger project effort, with a focus on several specific survey questions and relevant parts of the interviews with participants. Previous work on this project has shown that there are no significant differences in confidence between returners and direct pathway students in regard to various engineering skills [8], although the confidence of students in their academic abilities has not previously been analyzed. There is evidence that undergraduate grades are significantly different for returners and direct pathway students, with returners' undergraduate grades being lower.…”
Section: Returnersmentioning
confidence: 93%
See 1 more Smart Citation
“…The work in this paper is part of that larger project effort, with a focus on several specific survey questions and relevant parts of the interviews with participants. Previous work on this project has shown that there are no significant differences in confidence between returners and direct pathway students in regard to various engineering skills [8], although the confidence of students in their academic abilities has not previously been analyzed. There is evidence that undergraduate grades are significantly different for returners and direct pathway students, with returners' undergraduate grades being lower.…”
Section: Returnersmentioning
confidence: 93%
“…An additional large-scale national study focused on returners in engineering masters' programs, with a specific focus on knowledge construction and how their work experiences impacted their learning in graduate classes [8], [9], [10]. The work in this paper is part of that larger project effort, with a focus on several specific survey questions and relevant parts of the interviews with participants.…”
Section: Returnersmentioning
confidence: 99%
“…This investigation was carried out through a mixed method study, utilizing a survey administered over the web using Qualtrics and a follow-up interview. The dataset originated from an earlier study that explored differences between Direct-Pathway and Returner graduate students [24,25]. This survey contained sections on demographics, academic information and experience, confidence, alignment of the master's degree with work, academic advising, and choice of school, future plans, and motivation for graduate study.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that, while they have been away from school for a substantial period of time, they experience similar self-efficacy to direct pathway students. They also do not appear to be at a disadvantage in the area of modern technology, even if it has been some time since they were in school [15]. It was also found that there were synergies between their previous work experience and their schoolwork [16], and that there was a greater likelihood that they would go through "disciplinary migration", or a change in major between their undergraduate and graduate studies [17].…”
Section: Returnersmentioning
confidence: 99%